escultor Tomás Altuna en Navarra: obras en la comarca Baztan-Bidasoa - Muruzábal del Solar, José María (Huarte de San Juan. Geografía e Historia, 2015)
In this article we analyze a set of funerary art, quite unknown to date, located in Navarre many cemeteries, namely the Baztan- Bidasoa area. In such an environment there is a substantial body of cemeteries with sculptural decoration due to hand stonemason and sculptor guipuzcoano Thomas Altuna, who worked much Navarra, Basque Country and elsewhere in the environment, in the first third of the 20th century. It is a mason who established his workshop next to the cemetery of San Sebastian Polloe specializing in marble working, but also practiced other stone sculpture. Bring to the catalog of works of the artist a set of 19 pantheons with sculptural adornment which, in any case, denote the hand of an interesting artist.